Cloning of phytase from Bacillus subtilis ASUIA243 in Escherichia Coli and Pichia pastoris system - Nor Soleha Binti Mohd Dali (Kulliyyah of Engineering,International Islamic University Malaysia, 2012)
Phytase gene from Bacillus subtilis ASUIA243 was amplified with specific primers for Escherichia coli and Pichia pastoris transformation. The amplified blunt-ended gene was cloned into cloning vector pCR®-Blunt II-TOPO® and transformed into Escherichia coli TOPlO competent cells, while the sticky-ended phytase gene was cloned into expression vector, pBAD TOPO® and transformed into E. coli DH5a. Restriction enzyme analysis was performed to confirm the insertion of the both genes. The blunt-ended phytase gene was purified and subcloned into pPICZaA vector. The positive recombinant vectors, pPICZaA-243HPp and 243H#l were sent for DNA sequencing and later analysed for the amino acid differences by comparing the sequencing result with the sequence obtained from the database. There were two amino acid differences, Nl47K and S207T in both genes. However the sticky-ended phytase gene contained deletion of a nucleotide and therefore was not selected for protein expression. The recombinant vector, pPICZaA-243HPp was linearized with Pmel and transformed into Pichia pastoris strain X-33. The transformants were grown on YPDS agar containing 1 OOμg/ml Zeocin. A few colonies were selected and replated on YPDS agar containing increasing concentration of Zeocin for selection of multi copy number of colonies. Colony-PCR was conducted to determine the stable integration of phytase gene in the Pichia host. Growth curve determination was conducted to determine the optimum time for the cell growth in glycerol. Three positive clones were selected for protein expression study. The study was conducted by culturing the clones in glycerol media for 28 to 29 hours and induced in methanol media for a few days. Samples were taken at 24 hours intervals and protein expression was monitored using SDS-PAGE, Western blot analysis and phytase enzyme assay. The expected band size for phytase from B. subtilis ASUIA243 should be 44.75 kDa but there was no expected band appeared on the polyacrylamide gel and nitrocellulose membrane. Cell lysis was conducted on the cell pellets and the supernatant was analysed by SDS-PAGE and Western blot. There was also no expected band appeared on the polyacrylamide gel and nitrocellulose membrane.